DVD Piracy as Alternative Media: The Scandal of Piracy, and the Piracy of “Scandal” in the Philippines, 2005–2009 - Mangahas, Maria F. (Kasarinlan: Philippine Journal of Third World Studies, 2015)
Some digital materials which are documentary of specific forms of social transgression comprise an apparent “market niche” for piracy. “Scandals” as unique commodities in the Philippines’s informal market for pirated disks are quite distinct from other digital entertainment, being originally candid/unstaged or “stolen”/taken without their subject’s knowledge and usually made to non-professional standards/equipment. Enterprisingly put on the market by pirate-entrepreneurs because of apparent consumer-audience interest in the content, such unique “reality” goods became conveniently available through networks of digital piracy outlets. In the context of consumption of pirated goods, the article reads “scandals” as expressive of everyday critique and resistance. The niche market for “scandals” functions as alternative media as these digital goods inherently evade government and (formal) corporate control as sources of news and entertainment. Indicators of the significance of “scandal” in the informal economy and the meaningful convergence between its piracy and consumer-audience demand are examined ethnographically: their translation into commodities through packaging, the range of sites for  consumers to access “scandals,” pirate-entrepreneurs’ sales strategies and standards, and how the market behavior of these “scandals” apparently responded to the unfolding of the social scandals in real time as current events—events that themselves were influenced by the popular circulation and piracy of these commodities. Three cases that took place between 2005–2009—“Hello Garci,” the “Kat/Kho sex scandals,” and the “Maguindanao massacre” DVD—serve as diverse examples, each with their own issues of authenticity, morality, and social effects consequent to piracy and consumption.